The Impact of Green Knowledge and Servant Leadership on Green Innovation through Green Self-Efficacy in Toba Caldera Geopark - Faris, Salman; Sagala, Lapiti Gokmatua; Wijaya, Elyzabeth; Albert, Albert; Hassim, Affendy Abu (Universitas Muhammadiyah Yogyakarta, 2025)
Research Aims: This study explores the contribution of green knowledge and servant leadership to green innovation, with green self-efficacy acting as a mediating variable, within the context of hospitality enterprises in the Toba Caldera Geopark region. It aims to examine how green self-efficacy mediates the relationship between green knowledge, servant leadership, and green innovation, addressing an empirical gap in geotourism-related studies in Indonesia.Design/Methodology/Approach: A quantitative approach was employed, with data collected from 80 hospitality employees operating in the Toba Caldera Toba Caldera Geopark area using structured questionnaires. The relationships among the variables were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM).Research Findings: The findings show that both green knowledge and servant leadership significantly and positively influence green self-efficacy. Furthermore, green self-efficacy is confirmed as a significant mediator in the relationship with green innovation. The indirect effects mediated by self-efficacy were found to be stronger than the direct effects, emphasizing the role of psychological confidence in fostering employee-driven innovation.Theoretical Contribution/Originality: This study contributes to the literature on sustainable hospitality management by highlighting the role of self-efficacy in green innovation models. It also expands the understanding of how green knowledge and servant leadership interact to promote environmentally friendly behavior in hospitality enterprises.Practical Implications: The study underscores the need for hotel management to enhance environmental training programs and adopt a servant leadership style that encourages green initiatives. It provides practical strategies for improving sustainability efforts in hospitality businesses, especially in geotourism destinations.Research Limitations/Implications: The study is limited by its geographic focus on the Toba Caldera Geopark region, and its findings may not be directly applicable to other regions or sectors. Future research with a broader sample and across diverse geotourism contexts is needed to generalize the results.